Application potential of a new kind of superconducting energy storage/convertor. (June 2022) - Li, Wenxin; Yang, Tianhui; Li, Gengyao; Xin, Ying
Abstract: Our previous studies had proved that a permanent magnet and a closed superconductor coil can construct an energy storage/convertor. This kind of device is able to convert mechanical energy to electromagnetic energy or to make an energy conversion cycle of mechanical → electromagnetic → mechanical. In this study, we focus on the investigations into the application potential of this kind of device. First, we confirmed our proposed optimized configuration with theoretical analysis and experiments on a scaled-up testing platform. Furthermore, a new prototype with a large permanent magnet and a grouped coil composed of three separated closed superconducting coils was built and tested. It was proved that both practical meaningful mechanical force and energy storing capacity could be achieved with this kind of device by using enlarged pair of magnet and superconductor coil. Finally, we investigated the attenuation characteristic of the current in the superconducting coil at a stable energy storing state for a duration of about two hours, which shown the attenuation being practically tolerable for an energy storage with a typical charging-discharging cycle less than a few hours. It is concluded that this kind of device is of some advantages and promising application potentials as a short-term energy storage, particularly to replace fly-wheels in the case of mechanical → electromagnetic → mechanical conversion. Highlights: Energy storage/convertor with permanent magnets and a closed superconductor coil Interaction between permanent magnets and a closed superconductor coil Energy charging-discharging cycle of mechanical → electromagnetic → mechanical Investigation on application potential of the superconducting energy storage